Effects of transition cow management strategies on regulation of metabolism, immune signaling, and mammary function - Ylioja, Caroline M. (Kansas State University, 2019)
The weeks around parturition and the adaptation to lactation continue to present a challenge for the dairy cow and for the producers responsible for dairy cow management. Physiological adaptations to lactation can easily become dysregulated by factors such as insufficient nutrient availability to meet energy demands, oxidative stress, reduced immune competence, and excessive systemic inflammation, which can have lasting negative effects on the subsequent lactation. Recent literature shows that treatment strategies to reduce inflammation in early lactation have promoted sustained increases in milk production. Evaluation of transcriptional differences in mammary tissue due to anti-inflammatory treatment revealed no obvious differences to explain long-term effects, but differences in methylation of mammary tissue DNA warrant further investigation into potential epigenetic effects of inflammation mitigation. Management strategies to prevent excessive adiposity in transition cows are also often employed in commercial herds, as cows with excess body condition and lipid mobilization often have altered immune function and poor metabolic health in early lactation. MicroRNA, a type of non-coding RNA, facilitate communication and signaling between immune cells. We evaluated associations between maternal adiposity and microRNA in colostrum. Although no large-scale differences were detected in the colostrum profile of microRNA, further investigation of microRNA found in the mammary gland may help to determine the role of microRNA in the regulation of metabolism and immune signaling in the mammary gland, and to identify strategies to optimize cow health and production at the post-transcriptional level. Mitigation of the disparity between nutrients required by the dairy cow at the onset of lactation and the nutrients consumed through feed can also improve metabolic and immune function and promote the successful adaptation to lactation. We evaluated the effects of altered nutrient demand by reducing frequency of milking in early lactation. Although we did not observe large differences in glucose metabolism, reduced milking frequency did alter circulating glucose concentrations as well as some inflammatory markers in tissue and in circulation. Further development of strategies to optimize the resources available to the cow will help facilitate a successful navigation through this transition period and optimize both cow health and milk production.
Keywords: Dairy cattle; Inflammation; Lactation; Transition cows